An assessment on the floristic variety of Colchicum genus of Turkey in terms of morphological characteristics - ALTINKUT UNCUOĞLU, AHU; AYDİN, YILDIZ (ELSEVIER, 2021)
The study seeks to identify Colchicum species characterizing the morphological traits and to group the characters into species-specific clusters using Principal Component Analysis (PCA). Fifty-two Colchicum L. species, 25 of which are endemic, were characterized with important 36 morphological traits (21 for flower, 11 for leaf, 2 for corm and 2 for capsule). As a result of the morphological measurements, Colchicum technical certificate based on UPOV (The International Union for the Protection of New Varieties of Plants) was prepared and colour catalogue was created based on flowering time, perigon segments, perigon tube, anther, leaf, corm and capsule characters indicating the vast morphological differences among Colchicum species representing Turkish Flora. After the evaluation of measurements by PCA based on 36 morphological variables, it was observed that there is a clear separation between species according to their flowering time (spring, summer, autumn, late-autumn and winter) that can serve as a useful characterization feature to distinguish Colcicum species. Also, some characters, especially, perigon tube structure, perigon segments surface, perigon tube diameter, flower number, leaf number, leaf hairness, leaf surface, leaf shape were assigned as strong criterion to determine the Colchicum species.
Keywords: Colchicum L.; Colour catalogue; Morphological characterization; PCA; UPOV technical certificate; PHYLOGENY RECONSTRUCTION